Implementing health promotion programmes in schools: a realist systematic review of research and experience in the United Kingdom. (December 2015) - Pearson, M.; Chilton, R.; Wyatt, K.; Abraham, C.; Ford, T.; Woods, HB; Anderson, R.
Abstract Background Schools have long been viewed as a good setting in which to encourage healthy lifestyles amongst children, and schools in many countries aspire to more comprehensive, integrated approaches to health promotion. Recent reviews have identified evidence of the effects of school health promotion on children's and young people's health. However, understanding of how such programmes can beimplemented in schools is more limited. Methods We conducted a realist review to identify the conditions and actions which lead to the successful implementation of health promotion programmes in schools. We used the international literature to develop programme theories which were then tested using evaluations of school health promotion programmes conducted in the United Kingdom (UK). Iterative searching and screening was conducted to identify sources and clear criteria applied for appraisal of included sources. A review advisory group comprising educational and public health practitioners, commissioners, and academics was established at the outset. Results In consultation with the review advisory group, we developed four programme theories (preparing for implementation, initial implementation, embedding into routine practice, adaptation and evolution ); these were then refined using the UK evaluations in the review. This enabled us to identify transferable mechanisms and enabling and constraining contexts and investigate how the operation of mechanisms differed in different contexts. We also identified steps that should be taken at a senior level in relation topreparing for implementation (which revolved around negotiation about programme delivery) andinitial implementation (which centred on facilitation, support, and reciprocity—the latter for both programme deliverers and pupils). However, the depth and rigour of evidence concerningembedding into routine practice andadaptation and evolution was limited. Conclusions Our findings provide guidance for the design, implementation, and evaluation of health promotion in schools and identify the areas where further research is needed.